Synthesis of lactone-based conjugated polymers for recently emerging n-type organic thermoelectrics and electrochemical transistors - Alsufyani, MA (2023)
Conjugated polymers (CPs) have demonstrated remarkable potential as electroactive components for various electronic applications over the past decades. Electron-transporting (n-type) materials, in particular, have been recognized to be essential in recently emerging i) clean energy conversion applications for developing efficient thermoelectric generators and ii) in bioelectronics for metabolite sensing that rely on electron generation or for developing complementary circuits. However, current n-type materials have limited scope and poor performance when compared to their p-type counterparts. This work explores enhancing the performance of n-type materials for organic thermoelectrics (OTEs) and organic electrochemical transistors (OECTs), through strategic chemical design, and structure-property relationship elucidation. The polymer series designed in this work consists of electron deficient lactam and lactone building blocks, with a particular focus on the significance of the lactone unit on the polymer electron affinity (EA). The first two studies are dedicated to exploring and optimizing the thermoelectric performance of a series of six lactone-based n-type polymers. This was achieved through chemical design modulation of acene ring size, and side chain length/polarity, resulting in n-type polymers with a state-of-the-art thermoelectric performance. The third study investigates the implementation of the earlier developed polymers in OECTs, particularly, focusing on the role of superoxide formation from electron transfer during polaron transport. This study demonstrates that turning off the thermodynamic favorability of this reaction prevents superoxide formation, leading to more stable and higher performing devices. The work of this thesis will offer guidance to the field, by demonstrating the advantages that can arise from designing n-type semiconducting polymers with high electron affinity, in the fields of OTEs and OECTs.